Post-Treatment of Microbrewery Effluent Through Coagulation and Rapid Filtration - Amanda Vedam Pupin; Cleber Pinto da Silva; Sandro Xavier de Campos (Orbital: The Electronic Journal of Chemistry, 2025)
This study evaluated the efficiency of double and triple filtration technology associated with coagulation as a post-treatment of microbrewery effluent from an anaerobic decant-digester (ADD). The coagulants used were ferric chloride (FeCl₃), polyaluminum chloride (PAC), and a tannin-based natural coagulant (TAN). The filtration rate used was 120 m³/m²/day. The efficiency of the system was evaluated through physicochemical parameters. The post-treatment, which combined coagulation and triple filtration, achieved removals of 98% for apparent color, 64% for Chemical Oxygen Demand (COD), 59% for Biochemical Oxygen Demand (BOD), 100% for Phenols, 99% for Total Phosphorus (TP), 77% for Total Kjeldahl Nitrogen (TKN), 96% for Total Suspended Solids (TSS) and 99% for Turbidity, with results varying according to the coagulant used. Results indicated that PAC was the most efficient coagulant at lower concentrations, followed by TAN and FeCl₃. The post-treatment system proved to be highly effective in contaminant removal, offering a promising solution for the treatment of microbrewery effluents.